2020
DOI: 10.14740/wjon1302
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Programmed Death-Ligand 1 Receptor mRNA as an Independent Negative Prognostic Factor for Triple Negative Breast Cancer

Abstract: Background Triple negative breast cancer (TNBC) (represents roughly 25% of all breast cancers in Yogyakarta) still has the worst survival compared to other breast cancer subtypes. Results from recent studies have shown that inhibition of programmed death-ligand 1 receptor (PD-L1) in TNBC patients is associated with better prognosis. Currently, data on PD-L1 expression and its prognostic value in Indonesian TNBC patients are still relatively unknown. This study aimed to investigate the expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
6
0
1
Order By: Relevance
“…Studies have confirmed the relationships between PD-L1 expression and worse survival; for example, a retrospective study in Indonesia demonstrated that the overexpression of PD-L1 in triple-negative breast cancer patients is associated with worse prognosis, independent of other established risk factors [11]. In our study, we identified a direct relationship between PD-L1 expression and tumor size.…”
Section: Discussionsupporting
confidence: 82%
“…Studies have confirmed the relationships between PD-L1 expression and worse survival; for example, a retrospective study in Indonesia demonstrated that the overexpression of PD-L1 in triple-negative breast cancer patients is associated with worse prognosis, independent of other established risk factors [11]. In our study, we identified a direct relationship between PD-L1 expression and tumor size.…”
Section: Discussionsupporting
confidence: 82%
“…Patients with TNBC responded better to neoadjuvant chemotherapy; however, OS and PFS still decreased [ 11 , 22 ]. Therefore, there was an urgent need to find alternative treatment strategies.…”
Section: Discussionmentioning
confidence: 99%
“…PD-1 binds to its two ligands, PD-L1 and PD-L2, which are expressed on the surface of tumor cells [ 10 ]. The breast tumors express PD-L1, and this expression is related to the negative receptor state [ 10 , 11 ]. In addition, studies have found that the treatment effect of patients with TNBC is significantly improved using anti-PD-1/PD-L1 single drug treatment (29,424,936).…”
Section: Introductionmentioning
confidence: 99%
“…Berdasarkan sebuah studi kohort retrospektif di Yogyakarta, ekspresi mRNA PD-L1 ditemukan pada seluruh pasien KPTN. Pada studi yang sama, 21% dari seluruh subjek menunjukkan overekspresi mRNA PD-L1 pada sel tumor dan merupakan faktor prognostik buruk 12 . Nilai prognostik PD-1/PD-L1 sendiri masih inkonsisten pada berbagai penelitian 13 , namun inhibisi terhadap PD-1/PD-L1 berdampak pada kesintasan yang lebih baik pada pasien KPTN 14 .…”
Section: Ekspresi Pd-1/pd-l1 Pada Kptnunclassified